1995
DOI: 10.1093/milmed/160.5.235
|View full text |Cite
|
Sign up to set email alerts
|

Reengineering Medical Treatment Facilities for TRICARE: The Medical Group Practice Model

Abstract: The purpose of this article is to propose a model for reengineering military community hospitals, as well as medical centers, to adapt to the extraordinarily rapid and complex changes that are being made to the Military Health Services System. This article analyzes the changes taking place and discusses how a particular organizational model, the Medical Group Practice Model, can enhance quality and patient satisfaction in a capitated managed care environment. The phased implementation, structure, and performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…These factors have caused MTFs throughout the DOD to look at their staffing models, determine if the current practice works, and in many cases to change their current approach to a more efficient model of staffing and operations. A review of the literature revealed that such changes are common in MTFs across the three services (Kongstvedt, 1997;Mcgee & Hudak, 1995). Similar to the previous model, " Provider Workforce Model for Regional TRICARE Networks" offers a framework for military leaders to use in developing staffing levels for MTFs (Lamar, Jacoby, Meyer, & Potter, 1997).…”
Section: Literature Reviewmentioning
confidence: 79%
“…These factors have caused MTFs throughout the DOD to look at their staffing models, determine if the current practice works, and in many cases to change their current approach to a more efficient model of staffing and operations. A review of the literature revealed that such changes are common in MTFs across the three services (Kongstvedt, 1997;Mcgee & Hudak, 1995). Similar to the previous model, " Provider Workforce Model for Regional TRICARE Networks" offers a framework for military leaders to use in developing staffing levels for MTFs (Lamar, Jacoby, Meyer, & Potter, 1997).…”
Section: Literature Reviewmentioning
confidence: 79%
“…The role of the nurse practitioner in managed care networks is multiple, flexible and based on interventions and outcomes of clinical practice. TRICARE demands a right-sizing of the workforce; models that can utilize nonphysician providers to a greater extent to provide beneficiary care (McGee & Hudak, 1995). Mundinger (1994) suggests that a collaborative model may be the best model as it reduces cost while enhancing quality and comprehensiveness.…”
Section: The Department Of the Air Forcementioning
confidence: 99%
“…General Hospital developed clinical management teams consisting of a physician, nurse, and administrator over ten years ago (McGee & Hudak, 1995). Reengineering, originally a business systems process change, has been used successfully in a variety of healthcare settings.…”
Section: Statement Of the Problem Or Questionmentioning
confidence: 99%
“…The culture created by the matrix organization has helped overcome such resistance at MAMC. Methods of countering resistance include obtaining commitment from the leadership and developing data demonstrating the need for change (Tunick, et al, 1997;McGee & Hudak, 1995). A system of promoting stakeholder input and involvement helps in dealing with resistance to reengineering initiatives (Tunick, et al, 1997;Pence, 1997).…”
Section: Statement Of the Problem Or Questionmentioning
confidence: 99%